Evolution of tribo-induced interfacial nanostructures governing superlubricity in a-C:H and a-C:H:Si films - Xinchun Chen (Nature Portfolio, 2017)
Hydrogenated amorphous carbon is a promising solid lubricant, but the underlying mechanisms surrounding its superlubricity remain unclear. Here the authors reveal that the attainment of a superlubricious state is dependent on the in-situin-situ formation of a nanostructured tribolayer through different carbon rehybridization pathways.